ANALISIS FUNDAMENTAL EKONOMI MAKRO SERTA PENGARUHNYA TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI - Woro Utari (Neo-Bis, 2008)
The research was based on reality that  gross national product is very important for supporting the economic growth rate.  This research aimed to test and analize the effect of macro economic fundamental to value added taxes.      The research type was an expalantory research, in nature that is a research method aim to discribe the effect or relationship among several variables, that were inflation, investation, interest rate, kurs, value added tax. The secondary and primary data were used. In analysis effect of each variables and analysis methode was used SPSS 11.    The result shown that simultanous inflation, investaiton, interest rate and kurs were affected significantly to value added tax and the partially all variable not significantly to value added tax.